Le Rime di Giovanni De'Mantelli di Canobio, detto Tartaglia (Cod. Grey 7.b.5) - Saxby, Cornelia Angelica (Italian Language and Literature, 2016)
This thesis presents, in a critical edition, the poems contained 1n Grey Ms. 7.b.5 of the South African Library in Cape Town. It is the fruit of the first serious investigation to be undertaken of this manuscript and of its contents. Before a reconstruction of the text could.be attempted, problems of authorship, provenance and dating of the manuscript itself as well as of the poems containing verifiable historical allusions required to be resolved. The results of these investigations may be summarized as follows: The Grey manuscript contains an anthology of fourteenth and fifteenth century poems originating, for the most part, in the areas of Emilia, Romagna and the Marches. This collection was compiled by an otherwise unknown courtier and rhymester, Giovanni de' Mantelli di Canobio, nicknamed Tartaglia, between 1473 and 1483. Of the 150 poems it contains, 145 are unique to the Grey Ms.